An Investigation on Information Search and Retrieval Skills of Undergraduate Students: A Case Study of Tai Solarin University of Education, Ijebu-Ode, Ogun State, Nigeria - Quadri, Monsuru Omotayo; Quadri, Ganiyu Oluwaseyi (MiddleBelt Journal of Library and Information Science, 2014)
This study investigates the information search and retrieval skills of undergraduate students in Tai Solarin University of Education (TASUED), Ijagun, Ijebu-ode, Ogun State, Nigeria. Descriptive survey design was adopted for this study and the population consisted of 10,713 undergraduates from the College of COSIT, COHUM, COSMAS and COAEVOT of the university. Simple random sampling was used to select a sample of 324 and the questionnaire was the main instrument used for the data collection. Data was analyzed using descriptive statistics consisting of table of frequency and percentage. The findings revealed that Google was often used with 252 (77.8%) response rates while the least respondents 12 (3.7%) never used the search engines at all. Majority of the respondents 170 (52.5%) agreed that the use of Boolean Operators (OR, AND, NOT) were employed when searching for information while 20 (6.2%) respondents disagreed that advanced search strategies were employed when searching for information. Poor internet connectivity, erratic power supply, lack of technical know-how was the major difficulties faced by the respondents. The Google and Google scholar are important sources of searching and retrieving information by the university undergraduate students in TASUED. The search engines employed had tremendously contributed to the information retrieval for academic purposes. Undergraduate students should endeavour to equip themselves with the necessary ICT skills needed for this information age.